Macroporosity of a typic argiudoll with different cropping intensity under no-tillage - Behrends Kraemer, Filipe; Morras, Hector (Universia, 2019)
Soil macropores are dominant pathways of water flow and their impact on hydraulic properties is directly related to their geometrical and topological characteristics. A number of field and micromorphological analysis have shown that agriculture management under no-tillage promotes the development of a microstructure characterized by platy aggregates and horizontal planes in the topsoil, together with a densification at a subjacent layer, thus raising questions about physical properties and water dynamics under this system of cultivation. Moreover, scarce information is available about the evolution of pore architecture and physical parameters in soils under no-till with different cropping intensity. The objective of this work was to evaluate soil porosity in a silty loam A horizon of a Typic Argiudoll (Monte Buey series) of northern Pampa Region (Argentina) under two no-tilled contrasting managements: Good Agricultural Practices (GAP) –highly intensified cropping sequence including corn and wheat in addition to soybean-, Poor Agricultural Practices (PAP) -simplified crop sequence, with predominance of soybean- and a Natural Environment (NE) as reference. Topsoil porosity was assessed by micromorphology, micromorphometry and water retention curves approach, and the values obtained were related to some physical and chemical variables. Results of the morphological analysis revealed important differences between both agricultural treatments. In the surface layer in GAP, platy aggregates are thick and result from the cohesion of rounded microaggregates of biological origin; in PAP they are thin and dense, resulting mostly from compaction of individual soil particles and small microaggregates. A soil densification is evident in both agricultural treatments at 5-10 cm depth, although the morphology and size of aggregates and pores also differ between them. Micromorphometric analyses have shown differences in total macroporosity as well as in the size, morphology and orientation of macropores between both treatments. Macroporosity values obtained by digital methods were coincidently reflected by the pressure plate method. Porosity variables measured by digital analysis, in particular elongated pores and pore orientation, appear more sensitive than other soil properties (total carbon, aggregate stability, bulk density) in discriminating treatments. Although no-till cultivation led to the formation of platy microstructures and a decrease of soil porosity compared to NE, both agricultural treatments presented optimal values of Ks and water movement was not impaired. As expected, all morphological and analytical soil variables were better in the NE treatment. In addition, it was interesting to verify that the values of several parameters were close or similar between GAP and NE. Even when more intensified crop sequence (GAP) increases machinery traffic, morphological, physical and chemical soil properties were here improved compared to PAP. In this case, the higher proportion of different graminea into the agricultural cycle, besides its effect on the development of root biopores, seems to promote a higher fauna activity which effectively counteracts the vertical mechanical compression produced by traffic. These results suggest that, in addition to the known benefits of non-tillage on soil conservation, the improvement of various soil properties could be achieved by integrating this method of cultivation with suitable agricultural managements.